2015
DOI: 10.1111/jai.12680
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth of Boops boops (Linnaeus, 1758) in Izmir Bay, Aegean Sea, Turkey

Abstract: The present study was conducted to determine the age relationships in lengths and weights of Boops boops (Linneaus, 1756) in Izmir Bay, central Aegean Sea. A total of 932 specimens (503 females and 429 males) were caught by gillnet, trammel net and a combination thereof on a monthly sampling basis from November 2008 through October 2009. Total length and weight of sampled fish ranged from 11.3 to 27.9 cm and from 12.2 to 261.7 g, with a mean of 19.6 cm and 82.7 g, respectively. Length-weight relationships for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…In this study, the total length of B. boops caught in the Algerian east coast ranged from 10.1 to 30.9 cm and the maximum lifespan was 5 years with a quantitative dominance of ages 1 and 2. The size range of our specimens differs from the results obtained by other studies (Table 2), as for their life span (5 years), which is consistent with those obtained by Allam (2003); Benina (2015) and Kara and Bayhan (2015), close to those of El-Haweet et al (2005), El-Okda (2008) and differs from those of Khemiri et al (2005) and Monteiro et al (2006) (Table 2). The difference in the results obtained would probably be due to the sampling protocol used by each author, the study method as well as the sample size (Bariche, 2005).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the total length of B. boops caught in the Algerian east coast ranged from 10.1 to 30.9 cm and the maximum lifespan was 5 years with a quantitative dominance of ages 1 and 2. The size range of our specimens differs from the results obtained by other studies (Table 2), as for their life span (5 years), which is consistent with those obtained by Allam (2003); Benina (2015) and Kara and Bayhan (2015), close to those of El-Haweet et al (2005), El-Okda (2008) and differs from those of Khemiri et al (2005) and Monteiro et al (2006) (Table 2). The difference in the results obtained would probably be due to the sampling protocol used by each author, the study method as well as the sample size (Bariche, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…This project came after several alarm signals, drawn by different organizations, notably the FAO which following the study made on the state of the world's fisheries which had reported that in 2015, the Mediterranean with the Black Sea had displayed, the highest percentage (62.2%) of unsustainable stocks (FAO, 2018). In many parts of the Atlantic and Mediterranean, several studies have already been undertaken on the ecology and biology of this species (Valle et al, 2003;Mendes et al, 2004;Khemiri et al, 2005;Charif et al, 2008;Ghailen et al, 2010;Kara and Bayhan, 2015;Layachi et al, 2015), few works on their fisheries except Allam (2003) and Monteiro et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous study [10], the reproduction period of the bouge species in the Izmir Bay was late winter and early spring. The maximum gonadosomatic index value was 5.121 (February) for male individuals and 4.500 (February) for female individuals.…”
Section: Discussionmentioning
confidence: 84%
“…It is of great importance that knowledge of biological studies be reconfirmed in terms of optimal economic evaluation of present stocks. Most studies on age and growth biology of B. boops have been conducted in the Mediterranean region over the last 30-35 years [3][4][5][6][7][8][9][10]. However, the studies regarding its reproduction are very limited [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative length-width metric can yield measurements equivalent, or potentially superior, to traditional metrics. Many biologists have applied length-length or width-length relationships in the stock assessment of fish and marine invertebrates (Ricker 1973;Kara and Bayhan 2008). Alternative length or width measurements can easily be transformed directly to TL for use in fisheries management through a simple conversion equation.…”
mentioning
confidence: 99%